Financial Inclusion and Poverty Reduction: A Systematic Review of Literature in ASEAN - Rifadli D. Kadir; Muhibbuddin; Chitra Yuliashri Katili; Nurul Fadhilah (Department of Islamic Banking, 2026)
Purpose – This study aims to examine the role of financial inclusion in poverty alleviation within ASEAN countries by synthesizing existing scholarly evidence and identifying research trends, methodological patterns, key findings, policy implications, and future research gaps. Methodology – This study employs a PRISMA-guided Systematic Literature Review using the Scopus database. From 111 initial records, the screening process based on document type, source, language, and topic relevance resulted in 14 peer-reviewed studies selected for systematic analysis. Findings – The review shows that financial inclusion consistently contributes to poverty alleviation in ASEAN by expanding access to savings, credit, fintech, microfinance, and formal financial services. It also supports economic growth, reduces inequality in certain contexts, and helps address energy poverty. Most studies focus on Indonesia and apply quantitative econometric approaches, including panel data analysis, PVAR, FMOLS, AMG, and 2SLS. The dominant theoretical perspectives include endogenous growth theory, financial stability theory, financial innovation, and financial sector development, although several studies do not explicitly state their theoretical framework. Implications– Policymakers should strengthen inclusive access to finance, improve financial literacy, empower microfinance institutions, integrate financial inclusion into sustainable energy policies, and design context-sensitive programs for rural and vulnerable communities. Originality– This review offers a focused synthesis of the limited ASEAN literature on financial inclusion and poverty alleviation and identifies methodological, theoretical, and contextual gaps for future research.